Implications of registered insecticide reassessment for pasture pest management - Chapman, R.B.; Jackson, T.A. (New Zealand Plant Protection, 2010)
As part of an assessment of the risks costs and benefits of substances approved under the HSNO Act ERMA has established a list of potentially harmful materials for reassessment The initial Chief Executive Initiated Reassessment List contains 20 potentially hazardous substances of which 12 are insecticidal chemicals including some widely used in pastoral agriculture Pastoral intensification resulting from dairying and forage cropping appears to have stimulated an increase in insecticide use This is the reverse of the trend that coincided with the implementation of biological control and integrated pest management in the 1990s when there was a decline in the quantity of insecticides used in the pastoral sector The ERMA process follows international trends that have led to the deregistration of many pesticides based on old highly toxic chemistries effectively withdrawing them from international markets It is important for researchers and pest managers to be aware of the potential withdrawal of commonly used insecticides and develop alternative strategies for pest management